(3UdGI GdfLGI ef GdZQbs
(3ChdgG (B:s
(3Qhi GHf GdacgGfi GdeGdci ai cJGHg GdaLQ GdefjQ Cf bhekG QcHh SajfI s
(3Vef eLehY , JQJjHgG (B: (3GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B((3YGe (B9214) s
Keywords: (3GdbQGAGJ hGdJLhjOs